Diagnostic tool for collaborative monitoring of forest landscape restoration - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The diagnostic was presented to representatives from CFLRP projects. After receiving a completed diagnostic from one of the collaboratives, the USFS instructed to postpone all non-essential activities due to the extremely active 2020 wildfire season and the constraints posed by the COVID pandemic.